2021
DOI: 10.3390/su13158389
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Education in the Spanish Higher Education System: Faculty Practice, Concerns and Needs

Abstract: This article presents the results of the EDINSOST project in relation to the university faculty’s practice concerns and the need to embed sustainability education in the Spanish Higher Education system. Four questions were devised to determine (1) which conceptions the university faculty has about sustainability in the context of the Spanish higher education (2) what sustainability competencies the university faculty holds (3) the ways in which sustainability teaching strategies are implemented and (4) the way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…This data allowed us to obtain the qualitative evaluation of the MCS by another important stakeholder without a direct link to academia. In this sense, the external evaluation of competency maps was mostly done through the insights from the internal stakeholders of the educational process, such as teachers and trainers [55] or students [54]. This study contributes external insights from another very important stakeholder, which is graduates' potential employers, and sheds new light to the issue of the integration of sustainability in higher education.…”
Section: Discussionmentioning
confidence: 97%
“…This data allowed us to obtain the qualitative evaluation of the MCS by another important stakeholder without a direct link to academia. In this sense, the external evaluation of competency maps was mostly done through the insights from the internal stakeholders of the educational process, such as teachers and trainers [55] or students [54]. This study contributes external insights from another very important stakeholder, which is graduates' potential employers, and sheds new light to the issue of the integration of sustainability in higher education.…”
Section: Discussionmentioning
confidence: 97%
“…García-González et al ( 9 ) point out that although the FAO definition of a sustainable diet emphasizes that sustainable food should not only be environmentally friendly, but also culturally acceptable, accessible, and economically fair, these aspects are underestimated by the Spanish population ( 9 ). Research with university samples in Spain and other countries has also found that this population lacks a holistic view of the concept of a sustainable diet ( 13 15 , 19 ). These results suggest that it is crucial to develop training activities to foster a broader and more complex conception of food sustainability among the university community.…”
Section: Discussionmentioning
confidence: 99%
“…Universities have a great and undeniable potential as catalyzers for sustainability, being both formal learning institutions and places where informal, mutual influences and lay/expert knowledge meet ( 13 15 ). These organizations are also fundamental to achieving the SDGs proposed by the United Nations ( 16 – 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, engineering teachers have not received a complete training in all professional competencies, specifically in sustainability competencies. This increases their difficulty when it comes to embedding learning outcomes for education for sustainable development (ESD) in their subjects [22][23][24].…”
Section: Introductionmentioning
confidence: 99%